(untitled) - Radcliffe, Doug (Alameda, CA, 2003)
Here is the exclusive official book for the PC version of the best-selling XBox game, Halo: Combat Evolved, from Microsoft. The PC product refines and improves upon the Xbox version -- which many consider the "best first-person shooter ever" (EGM) -- with greatly enhanced multiplayer capabilities and new weapons and vehicles. This book, written by one of the most respected authors in the business, devotes considerable emphasis on the new aspects, including detailed maps for all the multiplayer levels and advanced multiplayer tactics. Complete walkthroughs, in-depth statistics, detailed maps, advanced multiplayer strategies, plus a full-color poster in every copy, make this book a "must-have" for Halo aficionados and newcomers.
Keywords: Computer games